FACTORS AFFECTING THE PROFITABILITY LEVEL (STUDY ON BUKU 3 CONVENTIONAL COMMERCIAL BANKS REGISTERED WITH THE FINANCIAL SERVICES AUTHORITY) - Viciwati, Viciwati (Dinasti International Journal of Management Science, 2021)
This research aims to test the influence of Third-party Funds (DPK), Capital Adequacy Ratio (CAR), Operational Income Operating Costs (BOPO), Loan to Deposit Ratio (LDR), and Non-Performing Loan (NPL) on the Profitability (ROA) at Conventional Commercial Banks Books 3 which are listed on Financial Services Authority (OJK) 2014-2018 period. This research is using the purposive sampling technique to collect data population from financial reports Conventional Commercial Banks Books 3 which are listed on OJK 2014-2018 period with the number of samples used were 16 banks. The data were analyzed using panel data regression using the fixed effect model. Hypothesis testing uses F-test statistic, coefficient of determination test (), and t-test statistic. The results showed that simultaneously of the five independent variables studied, significant impact on ROA. And partially of the five independent variables studied, there are two independent variables that negative and significant influence on ROA namely BOPO and NPL. While three independent variables do not positive and do not significantly affect ROA namely DPK, CAR, and LDR. The Contribution of all independent variables is 89,7125% and the rest of the value 10,2875% can be explained by another variable outside this research model.